Economic Liberalization and Indian Economic Growth: What's the Evidence? - Kotwal, Ashok; Ramaswami, Bharat; Wadhwa, Wilima (Journal of Economic Literature, 2011)
India's growth and poverty performance over the last three decades has been a subject of great curiosity. Unlike the East Asian countries, India's growth spurt is not associated with exceptionally high domestic savings or foreign capital inflows or manufacturing exports. So what triggered the change in the growth trajectory? Did the market liberalization policies of the 1990s help? How have the initial conditions shaped the process? And how has the “Indian model” impinged on India's central problem of mass poverty? This paper surveys the literature and offers its own assessment of the drivers of change. (JEL I32, O13, O14, O15, O21, O47)